Manifestations of Pulmonary Tuberculosis in the Eye - Khalid Mehmood Najmi, Syed Ali Haider, Hussain Ahmad Khaqan (Pakistan Journal of Ophthalmology, 2011)
Purpose: To study the manifestations of pulmonary tuberculosis in the eye. Material and Methods: A prospective study was conducted at department of Ophthalmology PGMI / LGH Lahore from April 2006 to July 2007. Patients with established diagnosis of Pulmonary Tuberculosis were recruited from the TB DOTS programme. Complete ocular examination including best corrected visual acuity (BCVA) anterior segment and dilated posterior segment examination was carried out on all patients. Results: BCVA was 6/24 or better in 59% patients and 6/36 or worse in 41% patients. Color vision was defective in 24 patients (12 %). Interstitial keratitis was found in 2 (1%) patients, anterior uveitis in 9 (4.8%), periphlebitis in 17 (9%), choroiditis in 26 (14%), vitritis in 16 (8.6%), vitreous hemorrhage in 8 (4%), NVE in 14 (7.4%), and optic atrophy in 7 (3.7%) patients. Conclusion: Significant proportion of patients on treatment for Pulmonary Tuberculosis showed signs of present or past ocular inflammation.